IMPLEMENTASI PENDIDIKAN INKLUSIF PADA PROGRAM KESETARAAN PAKET C DI PKBM BINA KREASI KELURAHAN TANGKERANG TIMUR KECAMATAN TENAYAN RAYA KOTA PEKANBARU - Alfino Alfino; Daeng Ayub Natuna; Muhammad Jaiz; Anggoro Piko (Universitas Tanjungpura, 2022)
children with certain limitations and other children unite regardless of their respective limitations. The problem In the teaching and learning process, tutors tend to not pay attention or adjust to the conditions of children with special needs, this certainly has an impact on the learning desires and expectations of children with special needs. This type of research is a descriptive study and a qualitative approach that aims to provide a systematic description of the current situation in the object of research, namely by implementing inclusive education. From the results of the research above, we can see indicators that those who use the Implementation of Inclusive Education in the Package C Equivalence Program at Pkbm Bina Kreasi, Tangkerang Timur Village, Tenayan Raya District, Pekanbaru City are the fields of study / tutor subjects at PKBM are appropriate, not appropriate, but tutors PKBM Bina Kreasi is able to adjust the learning material that is conveyed to students. The learning process at PKBM Bina Kreasi has been designed according to the syllabus. In the learning process, the PKBM Bina Kreasi tutor applies a learning model. The learning model applied by the tutor at PKBM Bina Kreasi is based on the child with special needs so that the tutor can easily convey learning and the child can easily absorb the learning delivered by the tutor during the teaching and learning process. The conclusion in terms of the sub-indicators of having educational qualifications, and having academic competence states that the number of tutors who teach at PKBM Bina Kreasi is 9 people, of which 3 are men and 6 are women.